Transformation of Artistic Imageries of the World and National Cinema in the Era of Postmodern - O. V. Andreeva (Дискурс, 2021)
Introduction. In the last third of the 20th century new trends appeared in various spheres of public life. That made possible to characterize this time period as the era of postmodern. The culture processes of this period were called postmodernism. Despite significant research on the topic and phenomenon of postmodernism, it remains a subject of discussion, which makes the problem of its further study actual. The article reveals postmodernism through the prism of new accents in the disclosure of artistic images in world and national cinema. Transformation of artistic imageries in the cinema is analyzed in the historical, cultural and philosophical terms, which is an element of novelty of the article.Methodology and sources. The methodology is based on the analysis of sources and literature, taking into account interdisciplinary approaches. Historical, comparative, systemic and semiotic research approaches are used. The author also used an integrated approach (formational and civilizational), which gives us a new perspective in understanding cultural phenomenon.Results and discussion. The artistic images of the world cinema are conceptually considered in a comparative analysis with the pre-war and post-war eras. The theoretical basis is the work of foreign (F. Jameson, J. Lacan) and domestic researchers (V.M. Dianova, I.P. Ilyin, N.A. Khrenov). National cinematography in the postmodern era is studied in the context of global and European processes, which makes possible to identify its general and specific feature.The results of the study show that in the last third of the 20th century, a significant transformation of artistic imageries took place in the world and in the national cinematography. It was based on unprecented social and cultural processes that led to profound behavioral and discursive changes. National cinematography reflected in its development global trends. However, the cultural development of Russian society in the postmodern era coincided with a systemic crisis and the collapse of statehood. That determined the specificity of Russian postmodernism, its philosophical and cultural orientation. In this regard, the urgency of the problem of studying the cultural dynamics of spiritual processes of the late Soviet period and post-Soviet Russia, including in cinematography, is obvious.Conclusion. Cinematography as one of the most important phenomena fully reflects the dynamics of modern spiritual processes. Therefore, the study of artistic imageries of the world and national cinematography in the postmodern era is of significant research interest. The use of interdisciplinary and integrated approaches, taking into account the achievements of foreign and national researches, allows us to get a multidimensial picture of the spiritual transformation of the society. An unbiased understanding of the cultural and historical experience of the last third of the 20th century makes it possible to better understand the modern world, because without an analysis of the past, both the present and the future are inconceivable.